The Influence of Discipline, Work Stress, and Job Satisfaction on Special Education Teachers’ Performance at Talenta Center School - Syifa Hayatillah; Siti Zubaidah; Saiful Anwar (Actual Insight, 2025)
Educator performance is a key determinant of educational quality in special needs schools, where teaching demands are characterized by high emotional labor, complex instructional responsibilities, and intensive student support. However, empirical studies that examine educator performance through an integrated organizational and psychological perspective particularly focusing on work discipline, work stress, and job satisfaction remain limited in the context of private special needs institutions. This study aimed to analyze the effects of work discipline, work stress, and job satisfaction on educator performance at Talenta Center Special Needs Schools. A quantitative survey design was employed, involving 134 educators selected as respondents. Data were collected using structured questionnaires and analyzed using multiple linear regression. The results revealed that work discipline and job satisfaction had positive and significant effects on educator performance, while work stress had a negative and significant effect. These findings indicate that educator performance in special needs schools is shaped by the interaction of organizational discipline, psychological well-being, and work-related pressures. The study highlights the importance of strengthening work discipline, implementing effective stress management strategies, and fostering job satisfaction to enhance educator performance and support the delivery of high-quality special education services.